Phytotherapy knowledge and practices among health care undergraduates: A cross-sectional study (Research, Society and Development, 2021)
Objective: Evaluate the knowledge and practices in Phytotherapy among students in the health area in Campina Grande - PB. Methodology: Cross-sectional exploratory and descriptive study, carried out using an appropriate questionnaire. After descriptive statistical analysis, the Chi-square and Fisher's exact tests were used to assess the existence of associations between the variables, with a significance level of 5%. Results: Among the interviewees (n=214), most had already used some medicinal plant or derivative (68.7%) and had no training in herbal medicine (89%). Among students from the second half of the courses, there is a greater use of herbal medicines (78.9% vs. 63.6%); and those who use herbal medicines also recommend them more to third parties (87.8%) than to those who do not use them (52.6%). Regarding the behavior of "indicating phytotherapy", this is performed more by students who are not natives of Campina Grande (56.5% x 40.7%) and who participated in some training in the area (66.7% x 43, 4%). Conclusion: The interviewed students have a profile, in terms of practices and knowledge about phytotherapy, very similar to the general population, which highlights the importance of developing strategies to approach phytotherapy among students in the health field.